The Effect of Working Capital Ratio, Accounts Receivable Duration, and Solvency Ratio on the Financial Performance of Healthcare Companies with Inflation as a Moderating Variable - resa selfana; Lestari Wuryanti; Hiro Sejati (International Journal of Management, Economic and Accounting, 2026)
This study aims to examine and analyze the effect of Working Capital Ratio, Accounts Receivable Duration, and Solvency Ratio on the Financial Performance of Healthcare Companies with Inflation as a Moderating Variable. The approach used is quantitative, the population of this study is healthcare sector companies listed on the Indonesia Stock Exchange for the period 2021-2023, the sampling technique uses purposive sampling technique with a total sample of 14 companies. Hypothesis testing is conducted using panel data analysis and MRA. The results of the analysis indicate that the Solvency Ratio (DER) has a negative and significant effect on Financial Performance, Inflation moderates the relationship between the Solvency Ratio and Financial Performance significantly in a positive direction, Working Capital Ratio, Accounts Receivable Duration and Solvency Ratio simultaneously have a significant effect on Financial Performance, Working Capital Ratio (CR) does not have a significant effect on Financial Performance, Accounts Receivable Duration (DSO) does not have a significant effect on Financial Performance, Inflation does not moderate the relationship between Working Capital Ratio and Financial Performance, Inflation does not moderate the relationship between Accounts Receivable Duration and Financial Performance.